Dragon Fruit (Hylocereus polyrhizus) Cultivation in Pareugreug Hill, Pajagan Village: A Community Service Case - Budiarto, Rahmat; Mubarok, Syariful; Kusumiyati; Farida; Sutari, Wawan; Soleh, Mochamad Arief; Nuraini, Anne; Djaya, Luciana; Rasiska, Siska; Istifadah, Noor (Indonesian Journal of Community Services Cel, 2025)
Red-fleshed dragon fruit (Hylocereus polyrhizus) has gained popularity in Indonesia due to its nutritional value and economic potential. This work was aimed to report the community service about dragon fruit cultivation in Pareugreug Hill, Pajagan Village, Sumedang. The consultation was held during January to February 2025. This study documented the sustainable agricultural practices such as implementation of vegetative propagation, organic fertilization, and natural climbing supports for dragon fruit. At 15 months after planting, 5% of the 400 plants had entered the fruiting stage. However, challenges such as pathogen attacks remain, requiring further research to improve disease management and ensure sustainable cultivation.